BUSINESS MARKETING TIPS PECEL LELE TENT SHOP ALL THE WAY OF CROSS NORTH SUMATRA LIRIK DISTRICT INDRAGIRI HULU REGENCY RIAU PROVINCE - Farin Kharisma; Eni Yulinda; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research on pecel lele business marketing tips in the tent stalls and was held on 17 June to 3 July 2015 along the East Sumatera Lirik District of Indragiri Hulu Regency Riau province. The purpose of this study was to describe the business activities pecel lele in the tent stalls and separately describe the factors that influence marketing efforts in the shop tent pecel lele. The method used in this study is a survey method.The results showed that the tent stalls pecel lele is a trading business meal is done in the afternoon until midnight and even some are open at 17:00 pm until 24.00 pm which amounted to 6 waung pecel lele, while the business is located near the dismissal of intercity public transport this province which amounted to 3 stalls open at 15:00 pm until 3:00 pm, because the location is always crowded prospective buyers. The existence of business pecel lele by employers pecel lele in the Trans Eastern Sumatra District of Lirik Indragiri Hulu influenced by some external factors: the probability that the rate of population growth, innovation cookware, policies and government's role in business development pecel lele, where location support, availability raw materials, consumer purchasing power, the development of the marketing area. Internal factors are the factors by an employer to conduct business activities tent stalls pecel lele. the results of research conducted by the tips of respondents different merchants, among them there maid, facilities, strategic location, quality of product, service / service and cleanliness.Keywords: Marketing Tips, External Factors, Internal Factors.